Research results utilization in vocational education policy making in Malaysia - Libunao, Wilfredo Herrera (Serials Publications, 2016)
This research assessed the utilization of research findings in technical and vocational education (TVE) policy development process and determined ways to bridge the gap between TVE research and policy making. It employed mix research method: qualitative (focus group discussion, elite interview and in-depth interview; quantitative (using survey questionnaire). The questionnaires were administered to 105 purposively-chosen respondents, who were TVE researchers from 6 polytechnics and 4 universities. The qualitative and quantitative data were analysed using NVIVO version 8 and descriptive statistics using SPSS version 13, respectively. Results show that 77.1% of the respondents do not have knowledge of TVE policy making process and only few (4.8%) have knowledge on whether their research findings were used in TVE policy making. Analysis of the twelve-item-inquiry on the extent of research results utilization indicated that research findings are seldom used in TVE policy making. Several major reasons why research findings are seldom used in policy making were identified. This study was able to identify important things that the researchers can do to promote utilization of their research findings and bridge the gap between research and TVE policy development.